THE EFFECT OF PLICKERS-ASSISTED TEAM GAMES TOURNAMENT ON STUDENTS’ LEARNING OUTCOMES AND CHARACTERS IN SOCIAL SCIENCE LEARNING SUBJECT - Muhammad Ali; Abdul Azis Muslimin; Muhammad Basri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper (1) describes students’ character values through the Team Games Tournament learning model assisted by Plickers media, (2) describes students’ learning outcomes through the Team Games Tournament learning model assisted by media Plickers, and (3) describes the effect of the Plickers media-assisted Team Games Tournament learning model on students’ character values and learning outcomes simultaneously. The research is quasi-experimental research with a non-equivalent control group design. The population of the research was all the fifth-grade students of SD Cluster 1 in Manuju. Through random sampling technique, the researcher selected the fifth-grade students of SD Inpres Pattallikang and SD Inpres Tanakaraeng as research samples. Data were collected through questionnaires and tests, and subsequently analyzed through t-test (paired sample t-test). The research results indicate that there were differences in students’ character values and social science learning outcomes in the control and experimental classes. The average character values and learning outcomes in the experimental class were higher than the control class. Thus, it can be concluded that the Team Games Tournament learning model influences the character values and students’ social science learning outcomes.